Nusinersen by subcutaneous intrathecal catheter for symptomatic spinal muscular atrophy patients with complex spine anatomy. Issue 1 (19th October 2021) - Carson, Vincent J.; Young, Millie; Brigatti, Karlla W.; Robinson, Donna L.; Reed, Robert M.; Sohn, Jihee; Petrillo, Marco; Farwell, Wildon; Miller, Freeman; Strauss, Kevin A.
Abstract: Introduction/Aims: Intrathecal administration of nusinersen is challenging in patients with spinal muscular atrophy (SMA) who have spine deformities or fusions. We prospectively studied the safety and efficacy of nusinersen administration via an indwelling subcutaneous intrathecal catheter (SIC) for SMA patients with advanced disease. Methods: Seventeen participants commenced nusinersen therapy between 2.7 and 31.5 years of age and received 9 to 12 doses via SIC. Safety was assessed in all participants. A separate efficacy analysis comprised 11 nonambulatory, treatment‐naive SMA patients (18.1 ± 6.8 years) with three SMN2 copies and complex spine anatomy. Results: In the safety analysis, 14 treatment‐related adverse events (AEs) occurred among 12 (71%) participants; all were related to the SIC and not nusinersen. Device‐related AEs interfered with 2.5% of nusinersen doses. Four SICs (24%) required surgical revision due to mechanical malfunction with or without cerebrospinal fluid leak (n = 2), and one (6%) was removed due to Staphylococcus epidermidis meningitis. In the efficacy analysis, mean performance on the nine‐hole peg test improved in dominant (15.9%, P  = 0.012) and nondominant (19.0%, P  = 0.008) hands and grip strength increased by 44.9% ( P  = 0.031). We observed no significant changes in motor scales, muscle force, pulmonary function, or SMA biomarkers. All participants in the efficacy cohort reported one or more subjective improvement(s) in endurance, purposeful hand use, arm strength, head control, and/or speech. Discussion: For SMA patients with complex spine anatomy, the SIC allows for reliable outpatient administration of nusinersen that results in meaningful improvements in upper limb function, but introduces risks of technical malfunction and iatrogenic infection.